If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8a + 3b) + -14 + -1(6b + a) = 0 Remove parenthesis around (8a + 3b) 8a + 3b + -14 + -1(6b + a) = 0 Reorder the terms: 8a + 3b + -14 + -1(a + 6b) = 0 8a + 3b + -14 + (a * -1 + 6b * -1) = 0 8a + 3b + -14 + (-1a + -6b) = 0 Reorder the terms: -14 + 8a + -1a + 3b + -6b = 0 Combine like terms: 8a + -1a = 7a -14 + 7a + 3b + -6b = 0 Combine like terms: 3b + -6b = -3b -14 + 7a + -3b = 0 Solving -14 + 7a + -3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 7a + 14 + -3b = 0 + 14 Reorder the terms: -14 + 14 + 7a + -3b = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 7a + -3b = 0 + 14 7a + -3b = 0 + 14 Combine like terms: 0 + 14 = 14 7a + -3b = 14 Add '3b' to each side of the equation. 7a + -3b + 3b = 14 + 3b Combine like terms: -3b + 3b = 0 7a + 0 = 14 + 3b 7a = 14 + 3b Divide each side by '7'. a = 2 + 0.4285714286b Simplifying a = 2 + 0.4285714286b
| (x+6)(x+3)= | | (x+8)(x-4)= | | halfy+3=7 | | a+2=-3 | | -3+5x-12=15 | | 32k-4=-5k-32 | | 2c-5=7 | | (7x+3)(x+7)= | | 0.3b=4 | | x+y=-9 | | x-2y=-28 | | 5x-5=6x+4 | | 4(a+7)=65.6 | | .5y=-6 | | 50.4=8c-8 | | 4e-3=13.4 | | 7x+2-3x-5=10 | | 3x^2-57x=0 | | 7(x-6)=-7 | | 4+2(3-x)=3(2x+7)+5 | | -16a=30a+24 | | 4(a+4)=32 | | 64=8c-8 | | 8e-3=13 | | w^2+5w+6=0 | | x^2=9-7x | | b^2+9=6b | | v^2-2v+1=0 | | halfx=5 | | c^2+5c-24=0 | | 5x-(2x-89)=164 | | x^2+7x-9=0 |